A Modest Proposal for Preventing the Votes of People with Short Life Expectancy from Being a Long-Term Burden to Their Country - Ognjen Arandjelović (Social Sciences, 2023)
In response to the growing social discontent regarding what is perceived as generational injustice, due to younger generations of voters facing long-term negative consequences from issues disproportionately decided by the votes of older generations of voters, there have been suggestions to introduce an upper age voting threshold. These have been all but universally dismissed as offensive and contrary to basic democratic values. In the present article, I show that the idea is in fact entirely consonant with present-day democratic practices and far from without a precedent. Hence, I describe how the aforementioned generational injustice can be rectified using a simple vote-weighting scheme which is easy to implement and interpret. Lastly, I discuss the societal effects that this alteration of the voting system would have on the distribution of the origins of political power.